Nursing approach for sexual assaults against women - ŞİŞMAN, FATMA NEVİN (My University, 2013)
Violence against women is a complex and multi-dimensional phenomenon and is recognized as an important public health problem. Sexual assault, which is a type of violence against women, causes serious and long-term medical, psychological, legal and social issues. Generally, nurses are one of the first health professionals to meet the victims. For this reason, the nurses have an important position for identifying the victim, providing support and trust, and guiding treatment and legal processes. In this article, the key points of nursing approach for the victims of sexual assault are reviewed.
Keywords: Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Sexual assault; nursing; woman; HEALTH OUTCOMES; VICTIMS